Ecology crafts for kids 50 great ways to make friends with planet earth - Needham, Bobbe. frey50 (New York : Sterling Pub., 1998)
Provides instructions for a variety of craft activities using recycled materials or items from nature and teaching a respect for the environment.
"A Sterling/Lark book."
Includes index.
Keywords: Ecology -- Juvenile literature; Nature craft -- Juvenile literature; Environmental protection; Nature craft; Handicraft